ANALISIS PANDANGAN AHMAD HASSAN TERHADAP NASAKH DALAM AL-QUR’AN - Ahmad Zuhri; Jidin Mukti (Fakultas Ushuluddin dan Studi Islam, 2021)
AbstractThe knowledge of abrogation is a very important aspect in interpreting the verses of the Qur'an. The scholars agree on the application of arbitration in Islamic law. In an effort to accept the concept of intra-Qur'anic abrogation, experts have different opinions, some accept it and some reject it. One who rejects the existence of texts among the verses of the Qur'an which is the interpreter of the archipelago is Ahmad Hassan. Hassan's argument against the existence of nasakh in the Qur'an has similarities in several aspects with Rashid Rida. So that Hassan's argument pattern has a common ground with Abu Muslim Al-Isfahani's argument about texts in the Qur'an.